Evaluation of Variable Compressor Technologies - Grigoriadis, Panagiotis; Hoffmann, Alexander; La, Chi Binh (Frontiers in Mechanical Engineering, 2021)
A diverse set of technology solutions are in development for reducing vehicular CO2 emissions. Beside the conventional internal combustion engine, there are hybrid powertrains, fuel cells and full electric vehicles. The challenge is finding the right technology that can be quickly implemented into production as a cost effective solution. In addition to CO2 reduction during vehicle operation, the impact of CO2 in the production and recycling of future vehicles must also be considered. From this perspective, the role of turbocharging is evolving, becoming more important for the future. It is an enabler for mature technologies known to improve engine efficiency like Miller timing, lean burn, increased exhaust gas recirculation (EGR) dilution and exhaust heat recovery. As a boosting device, improved turbocharging can also benefit other powertrain types like fuel cells. All previously mentioned applications benefit from wider compressor maps and higher compressor ratios. To achieve an extension of the performance map to areas of low mass flow rate, different methods have been discussed with the two most promising being trim reduction introduced by IAV’s Variable Trim Compressor (VTC) and swirl generation. The most common device for inducing a swirl onto the incoming airflow is to use swirl generating wings in front of the compressor wheel. However, Iwakiri explained that putting a single plate in front of the compressor wheel disturbs the recirculating flow, which acts positively to extend the compressor map. On this basis, plates were developed that guide the strongly swirled back flowing air in such a way that they impose a swirl on the incoming air. Trim reduction is well known for its ability to shift the surge line and maintain compressor efficiency. To achieve this, a conical element before the compressor wheel guides the incoming flow to the inner area of the wheel resulting in reduced flow separation. An orifice can also achieve almost the same effect but with much less axial extension. The advantages and disadvantages of these measures are explained using numerical (CFD) and experimental (turbocharger test bench) to show the potential of each approach. In summary trim reduction using a conical geometry is still the best performing approach. However, considering package restrictions, an orifice is also a good choice. Whereas swirl producing principles have a moderate impact on shifting the surge line. The extension of high mass flow rate is also of interest and this study shows a simple method to improve the compressor performance map in this area. A combination of the measures to expand the map in both directions is conceivable and is presented here as a concept.